2012
DOI: 10.1016/j.ophtha.2011.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Assessment of Complications with Asymmetric or Sulcus Fixation of Square-Edged Hydrophobic Acrylic Intraocular Lenses

Abstract: Objective One-piece hydrophobic acrylic intraocular lenses (IOLs) are not indicated for sulcus fixation because of complications, such as uveitis-glaucoma-hyphema syndrome. Similar complications may also be observed with 3-piece lenses having a square optic edge on the anterior surface. The objective of this study was to provide pathological evidence of complications related to out-of-the-bag fixation of 1-piece or 3-piece hydrophobic acrylic IOLs with anterior and posterior square optic edges. Design Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…18 The methodology used was the same as in the current study; basically, pseudophakic cadaver eyes obtained from eye banks within the United States, implanted with different IOLs were evaluated. Anterior segment scanning of whole eyes with the same high-frequency ultrasound system or the high-resolution anterior segment magnetic resonance imaging was done, followed by gross examination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 The methodology used was the same as in the current study; basically, pseudophakic cadaver eyes obtained from eye banks within the United States, implanted with different IOLs were evaluated. Anterior segment scanning of whole eyes with the same high-frequency ultrasound system or the high-resolution anterior segment magnetic resonance imaging was done, followed by gross examination.…”
Section: Discussionmentioning
confidence: 99%
“…We were looking for any findings from imaging, gross, and histopathologic evaluation that could be related to out-of-the-bag fixation of the lenses. 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 A third case involved rubbing of the posterior surface of the iris by the inferior haptic of the IOL, which was in the bag but deformed. 6 Kirk et al 9 describe dramatic pathologic correlations of clinically reported complications of sulcus fixation or asymmetric bag-sulcus fixation of the haptics of single-piece hydrophobic acrylic IOLs. Pathologic findings demonstrated IOL decentration and tilt, pigmentary dispersion, iris transillumination defects and iris erosion, vacuolization, atrophy, thinning, and synechiae and were attributed to the square anterior and posterior surfaces of the optics and the thick bulky haptics of these IOLs when placed entirely or partially in the sulcus.…”
Section: Discussionmentioning
confidence: 99%